Genetic Studies and Breed Diversity of Kazakh Native Horses: A Comprehensive Review - Kabylbekova, D.; Assanbayev, T. S.; Kassymbekova, S.; Kantanen, Juha (The Running Line, 2024)
This comprehensive review analyzes the state of horse breeding in Kazakhstan, examining its historical context, current status, genetic studies, and future prospects. Drawing on historical records, government reports, academic studies, and genetic research, this review provides insights into the genetic diversity of Kazakh native horse breeds. The review traces the historical trajectory of horse breeding, explores its significance for the economy and culture, and discusses current population trends. Genetic studies reveal untapped potential for breed improvement. Kazakhstan's horse breeding faces opportunities for growth and development, requiring efforts to increase the horse population and harness genetic potential for productivity. This review emphasizes the need to preserve the gene pool of Kazakh native horses, ensuring sustainability and cultural significance.
Keywords: horse; animal husbandry; genetic resources; native breed